Dynamic consent: a royal road to research consent? : Extended essay - Bruns, Andreas; Winkler, Eva C. (Journal of medical ethics, 2024)
In recent years, the principle of informed consent has come under significant pressure with the rise of biobanks and data infrastructures for medical research. Study-specific consent is unfeasible in the context of biobank and data infrastructure research; and while broad consent facilitates research, it has been criticised as being insufficient to secure a truly informed consent. Dynamic consent has been promoted as a promising alternative approach that could help patients and research participants regain control over the use of their biospecimen and health data in medical research. Critical voices have focused mainly on concerns around its implementation; but little has been said about the argument that dynamic consent is morally superior to broad consent as a way to respect people’s individual autonomy. In this paper, we identify two versions of this argument - an information-focused version and a control-focused version - and then argue that both fail to establish the moral superiority of dynamic over broad consent. In particular, we argue that since autonomous choices are a certain species of choices, it is neither obvious that dynamic consent would meaningfully enhance people’s autonomy, nor that it is morally justifiable to act on every kind of consent choice enabled by dynamic consent.
Gesehen am 28.11.2024